Reuse of voucher specimens provides insights into the genomic associations and taxonomic value of wing colour and genitalic differences in a pest group (Lepidoptera: Tortricidae: Choristoneura). (6th January 2020) - French, Rowan L. K.; Lebunasin, Pasan N. A.; Brunet, Bryan M. T.; Lumley, Lisa M.; Cusson, Michel; Levesque, Roger C.; Sperling, Felix A. H.
Abstract: Subtle morphological differences can be essential to diagnosing closely related species, and an understanding of the genetic basis of these characters can contribute to understanding their divergences. We used voucher specimens from previous genetic analyses of population structure to subsequently analyse genome‐wide associations linking morphology to genetic variation in spruce budworms, a group of economically important and morphologically similar forest pests. In particular, we assessed the taxonomic value and genetic architecture of two morphological traits (wing pattern and genitalic spicule abundance) that have been reported to differ among spruce budworm species. Our results suggest that phallic spicule number has greater taxonomic utility than wing pattern for distinguishing Choristoneura fumiferana (Clemens) from Choristoneura occidentalis occidentalis Freeman and Choristoneura occidentalis biennis Freeman. However, there was considerable overlap among taxa for all phenotypic characters analysed. In a genome‐wide association study, wing pattern variation was significantly associated with four single nucleotide polymorphism (SNP) loci, including two adjacent SNPs. One SNP was flanked by sequence resembling RNA‐directed DNA polymerase from mobile element jockey‐like . This locus is a promising candidate for the study of wing pattern development in spruce budworms, as jockey‐like transposable elements and polymerases have documented roles in wing spot production in other Lepidoptera. Our study links classical taxonomic characters and genomic data to provide insights into the potential genetic architecture of species differences. It also demonstrates previously untapped morphological and taxonomic value in voucher specimens from earlier molecular genetic analyses. Abstract : We assessed the genetic architecture and taxonomic utility of morphological differences between three economically important spruce budworm taxa with parapatric ranges. One genitalic character (spicule abundance) was more useful than wing pattern for distinguishing species in western Canada but had no significant SNP associations. Four SNPs were associated with wing pattern variation among Choristoneura taxa, including a jockey‐like transposable element that influences spot colour differences in other Lepidoptera.